Experimental Investigation of the performance of a Desiccant Wheel (University of Khartoum Engineering Journal, 2022)
Desiccant cooling systems have the potential to make a major contribution to the reduction of bothCFC’s emissions and electricity peak load. An experimental investigation on the sensible effectiveness of adesiccant wheel is conducted. Measurements were made for a range of rotational speeds (0-5 rpm), regenerationtemperatures (50 to 60oC). A computer based calculation procedure using Excel worksheet was built, and appliedto estimate the effect of the desiccant wheel speed on the moisture removal and the sensible effectiveness. Thecalculations were based on the experimental data obtained during the experiment. The results succeeded indetermining the optimum rotational speed for the desiccant wheel, the sensible effectiveness, the moisture removalefficiency and the dehumidification coefficient of performance. It was found that the lower speeds gave betterresults than the higher ones.